Respostas comportamentais e autonômicas induzidas pela privação hídrica em ratos espontaneamente hipertensos - Pereira Junior, Emilson Donizete (2022)
Excess ingested NaCl can facilitate the onset and development of chronic diseases, including hypertension. The increase in salt palatability is usually the reason for excessive consumption of NaCl. Spontaneously hypertensive rats (SHRs), an animal model for the study of primary hypertension, ingest a greater amount of sodium when compared to normotensive strains. However, it was still unknown whether the increased preference for NaCl observed in SHRs would be related to changes in palatability to this ion. Considering that SHRs might have increased NaCl palatability, it would be important to investigate whether this effect would be specific for salty taste. Furthermore, there was no information in the literature whether gustatory stimulation could induce cardiovascular autonomic responses, as well as whether episodes of dehydration could alter the palatability profile and anxiety-like behavior and locomotor activity in SHRs. Therefore, the objectives of the present study were to investigate the: a) palatability to 0.3 M NaCl; b) sweet and bitter taste palatability profile; c) autonomic responses induced by gustatory stimulation; d) anxiety-like behavior and locomotor activity, in normotensive rats and SHRs under basal conditions and after a cycle of water deprivation and partial rehydration (WD-PR). Thus, SHRs and Holtzman normotensive rats were submitted to surgical procedures to implant of: a) an intraoral (IO) cannula, for taste reactivity test (TRT); femoral artery cannula, for mean arterial pressure (MAP) and heart rate (HR) recordings; c) intracerebroventricular cannula, for central administration into the lateral ventricle (LV). Intraoral (IO) infusion of 0.3 M NaCl produced a greater number of hedonic responses with no difference in the number of aversive responses in SHRs when compared with normotensive rats. Central blockade of AT1 angiotensinergic receptors (adrenergic receptor antagonist, losartan 100 ng/1 μl i.c.v.) abolished the ingestion of 0.3 M NaCl induced by the (WD-PR) protocol, while it reduced, only transiently (first 30 minutes of the 60-minute test) the number of hedonic responses to salty taste, with no changes in aversive responses. Losartana i.c.v. also reduced, only transiently (first 30 minutes), the number of hedonic responses to salty taste in euhydrated SHRs. Just like the salty taste, SHRs showed a similar number of hedonic responses to 2% sucrose IO and a similar number of aversive responses to quinine IO, either after WD-PR or in the euhydrated condition. Furthermore, these hedonic and aversive responses were greater when compared to normotensive rats. The IO infusion of the different tastes produced an increase in MAP and an increase in HR for 2% sucrose, 0.5M NaCl and quinine in normotensive rats and quinine for SHRs, this pressor effect was greater in SHRs, for all tastes. The administration of prazosin (1 mg/ml/kg i.v.) abolished the pressor effect induced by the IO infusion of all solutions tested, in both strains of rats. Furthermore, WD-PR produced the same profile of pressor responses to IO infusion of 0.3 M NaCl and distilled water compared to the euhydrated condition, both in normotensive animals and in SHRs. However, the pressor effect was greater in SHRs than in normotensives, regardless of the conditions of fluid and electrolyte balance. In the elevated plus maze (EPM) and open field (OF) test, SHRs show longer stay in the open arms and an increase in central locomotor activity, as well as the number of entries and time spent in the center of the open field apparatus, suggesting a less anxious pattern of behavior than normotensive rats. WD-PR produced no change compared to the respective baseline in anxiety-like behavior of normotensive animals and SHRs. However, after the period corresponding to the sodium appetite test, an increase in total locomotor activity was observed, as well as in the average speed covered in normotensive rats. In SHRs, after the end of sodium appetite, a significant decrease was observed in the time spent in the open arms of the EPM, a decrease in peripheral and central locomotor activity, number of entries and permanence in the center of the OF apparatus, in addition to an increase in the time spent on the periphery, when compared to your baseline condition (euhydrated). In summary, the results show that SHRs rats have an intense appetite and palatability to NaCl regardless of the conditions of the hydroelectrolyte balance, and part of this effect is due to the activation of central AT1 angiotensinergic receptors. As with salty taste, SHRs have an increase in hedonic responses to sucrose, and an increase in the number of aversive responses to bitter taste. This suggests that the enhanced response of SHRs to taste rewards does not correspond to a decreased response to a typical aversive taste. The WD-PR protocol did not alter anxiety-related behavior and locomotor activity in normotensive rats and SHRs. The present results also suggest that the affective component of taste induces cardiovascular responses mediated by the sympathetic nervous system.